2019
DOI: 10.1029/2018jb017035
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability Evolution of Tuffisites and Implications for Outgassing Through Dense Rhyolitic Magma

Abstract: There is growing evidence that outgassing through transient fracture networks exerts an important control on conduit processes and explosive‐effusive activity during silicic eruptions. Indeed, the first modern observations of rhyolitic eruptions have revealed that degassed lava effusion may depend upon outgassing during simultaneous pyroclastic venting. The outgassing is thought to occur as gas and pyroclastic debris are discharged through shallow fracture networks within otherwise low‐permeability, conduit‐pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…We find that the best results are found using 8 = 0.075 and that to within 5% accuracy, 0.06 ≲ 8 ≲ 0.1 is valid. This range of values is consistent with the range of 8 found for sintering or welding angular particles (Wadsworth et al, 2016;Heap et al 2019).…”
Section: The Permeability Of Impact Melt-bearing Brecciasupporting
confidence: 88%
“…We find that the best results are found using 8 = 0.075 and that to within 5% accuracy, 0.06 ≲ 8 ≲ 0.1 is valid. This range of values is consistent with the range of 8 found for sintering or welding angular particles (Wadsworth et al, 2016;Heap et al 2019).…”
Section: The Permeability Of Impact Melt-bearing Brecciasupporting
confidence: 88%
“…Tuffisite veins can be generated in new fractures or use pre-existing veins (Kendrick et al 2016). Sintering reduces both porosity and permeability with time (Wadsworth et al 2017;Heap et al 2019). Variable degree of sintering due to different P-T-t conditions can accordingly lead to a broad range of values of porosities and permeabilities in the tuffisite pyroclasts.…”
Section: Type 3 Dome Pyroclastsmentioning
confidence: 99%
“…The products of the Kilian eruption suggest that outgassing was significant in the magma column prior to each Vulcanian phase. Outgassing was likely promoted by enhanced bubble coalescence in a crystal-rich magma (e.g., Oppenheimer et al 2015;Lindoo et al 2017;Colombier et al 2020), brittle fracturing (Lamur et al 2017), and by fracture-like and intergranular connected pore space in tuffisite veins (Type 3 dome pyroclasts; Heap et al 2019). The dominant pathways of gas escape and fluid transport occur along interconnected vesicle clusters and tuffisite veins, and extensive precipitation of cristobalite appears to have been restricted to the exterior of the dome.…”
Section: Outgassing Vs Pressurization In Crystal-rich Trachytic Magmasmentioning
confidence: 99%
“…The spines extruded at Mt St Helens (USA) from 2004 to 2008, for example, were mantled by a 1-3 m-thick layer of cataclasites, breccias, and gouge (e.g., Cashman et al, 2008). Ash-filled fractures within conduits and lava domes-called J o u r n a l P r e -p r o o f Journal Pre-proof tuffisites-record episodes of brittle deformation, magma fragmentation, and outgassing (e.g., Tuffen et al, 2003;Castro et al, 2014;Saubin et al, 2016;Farquharson et al, 2016a;Gardner et al, 2018;Heap et al, 2019a). Faults are also commonly observed in sequences of volcanic rock (e.g., Gudmundsson, 2011;Holland et al, 2006;Bubeck et al, 2018) and localised compaction features have been observed in outcrops of tuff (e.g., Wilson et al, 2003;Okubo, 2014;Cavailhes and Rotevatn, 2018).…”
Section: Introductionmentioning
confidence: 99%